PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN PEMBERDAYAAN TERHADAP KARIR MENTOK (CAREER PLATEAU) DENGAN MEDIASI KEPUASAN KERJA - Rina Kurniawati, 1242020014 (Jurnal Mahasiswa Pasca Sarjana, 2014)
The test resulted of determination of transformational leadership and empowerment on job satisfaction that equal to 0.675, mean of 67.5% of the change in the variable job satisfaction could be explained by transformational leadership and empowerment variables in the model, while the remaining 32.5% was outside the model described above . While the test results transformational leadership determination, empowerment and job satisfaction on career plateau their determinated that meant 0.038 means 3.8% of the variable changes career plateau could be explained by their determinationÂ  variables of transformational leadership, empowerment and job satisfaction in the model, while the remaining 96.2% outside the model described above. Transformational leadership and empowerment proved to be positive and have a significant influence on job satisfaction. While transformational leadership, empowerment and job satisfaction did not significantly influence the career plateau Keywords: Transformational Leadership, Empowerment, Career Plateau and Job Satisfaction